Time to Track Endemic Diseases: Extraordinary Occurrence Diseases Shrinkage, Policy and Its Resources Management (2000-2018) in Indonesia - Al Fauzi Rahmat (Center for Health Policy and Management, 2021)
During 2000-2018 various disease outbreaks (extraordinary occurrences) continued to occur in Indonesia. Its endemic disease outbreak has fluctuated with other endemic, both infectious and non-communicable diseases. This epidemic's vulnerability gives concern for the government to try to deal with various outbreaks that hit Indonesian citizens. This paper aims to review and analyze frequent outbreaks and the extent of the Indonesian government's in tackling disease outbreaks – including policies and its health resources. By analyzing the successes and failures of policies that have occurred, our findings conclude that adequate governance is needed in dealing with disease outbreaks –including Diarrhea, DFH, and Measles. Therefore, the government's key concern is the need for new policies alternative in dealing with disease outbreaks (in cases; Diarrhea, DFH, and Measles), health budget ability, equitable development of health facilities, and equal medical distribution personnel.